Smart card research and advanced applications : 16th International Conference, CARDIS 2017, Lugano, Switzerland, November 13-15, 2017, Revised selected papers /: 16th International Conference, CARDIS 2017, Lugano, Switzerland, November 13-15, 2017, Revised selected papers. (2018) - Unknown
No abstract available